2003
DOI: 10.1007/s11892-003-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

New treatments for diabetic neuropathy: Symptomatic treatments

Abstract: Painful diabetic neuropathy is a common distressing and challenging condition. The mechanism or mechanisms involved in its pathogenesis continue to elude clinical scientists. As with other conditions of painful distal symmetrical neuropathic conditions, pain relief involves the use of a variety of analgesic and neuroleptic drugs, aimed at reducing either central responses to painful stimuli or at dampening spontaneous irritability of affected neurons. More recently, several therapies directed at putative patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…The study of the mechanisms of painful diabetic neuropathy has been mainly focused at the peripheral nervous system, whereas the central effects of the disease need to be more deeply addressed [1,5]. Several studies suggested that the spinal dorsal horn, the first relay station of the nociceptive pathway, is affected by diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the mechanisms of painful diabetic neuropathy has been mainly focused at the peripheral nervous system, whereas the central effects of the disease need to be more deeply addressed [1,5]. Several studies suggested that the spinal dorsal horn, the first relay station of the nociceptive pathway, is affected by diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment should include monofilament, vibratory, and pinprick tests. 14 Reflexes and the strength and flexibility of the toes, foot, and ankle should also be assessed. 10,14 Feet should be observed and palpated for any signs of ulcer risk (eg, hammer toes, bunions, calluses, tender areas).…”
Section: Assessmentmentioning
confidence: 99%
“…14 Reflexes and the strength and flexibility of the toes, foot, and ankle should also be assessed. 10,14 Feet should be observed and palpated for any signs of ulcer risk (eg, hammer toes, bunions, calluses, tender areas). Assessing for signs and symptoms of peripheral vascular disease, including pedal pulse quality, capillary refill, skin color and moisture, and ankle-brachial index, should be done.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations